PENEGAKAN HUKUM TERHADAP PENYALAHGUNAAN PENGANGKUTAN DAN NIAGA LIQUIFIED PETROLEUM GAS 3 KILOGRAM DI WILAYAH HUKUM KEPOLISIAN DAERAH SULAWESI TENGAH - Ferdiansyah Moh. Akbar (LEGAL OPINION, 2024)
The conclusions in this study are: (1) The process of law enforcement against the misuse of transportation and trading of 3 kg LPG based on Article 55 of Law Number 22 of 2001 concerning Oil and Gas as amended in Article 40 number 9 of Law of the Republic of Indonesia Number 11 of 2020 concerning Job Creation in the jurisdiction of Central Sulawesi POLDA in its implementation has been running properly. The obstacles faced by the Police in the process of law enforcement against the misuse of transportation and trading of 3 kg LPG gas based on Article 55 of Law Number 22 of 2001 concerning Oil and Gas as amended in Article 40 number 9 of Law of the Republic of Indonesia Number 11 of 2020 concerning Job Creation in the jurisdiction of Central Sulawesi POLDA come from human resource factors (police personnel), minimal facilities and facilities, and public awareness factors. ABSTRAK Kesimpulan dalam penelitian ini adalah: (1) Proses penegakan hukum terhadap penyalahgunaan pengangkutan dan niaga LPG 3 kg berdasarkan Pasal 55 Undang-Undang Nomor 22 Tahun 2001 Tentang Minyak dan Gas Bumi sebagaimana diubah dalam Pasal 40 angka 9 Undang-Undang Republik Indonesia Nomor 11 Tahun 2020 Tentang Cipta Kerja di wilayah hukum POLDA Sulawesi Tengah dalam pelaksanaannya sudah berjalan sebagaimana mestinya.